FORMULATION DEVELOPMENT AND CHARACTERIZATION OF A TOPICAL HERBAL CREAM CONTAINING ALOE VERA EXTRACT FOR ENHANCED PHOTOPROTECTIVE EFFICACY AGAINST UV-INDUCED SKIN DAMAGE - Ritu Sanwal; Devinder Kumar Maheshwari; Jeevanandham Somasundaram; Shaheena Sohi; Duggirala Mahendra; Rubel Ratnia; Indu Bala; Rohini Karunakaran (The Bioscan, 2025)
This study develops and evaluates a topical photoprotective cream containing Aloe vera extract because of its established soothing and moisturizing properties along with antioxidant effects. The developers chose appropriate excipients to create a cream that offered excellent spread ability alongside stability and skin compatibility features and selected Aloe vera as the main bioactive element because of its protective potential against ultraviolet (UV) radiation. The first step in formulation involved preparing an oil-in-water emulsion base which later received Aloe vera gel addition. A series of physicochemical tests evaluated the final cream product through assessments of organoleptic properties together with pH measurements and spread ability tests and viscosity measurements and stability tests conducted under different storage conditions. The spectrophotometric method measured in vitro sun protection factor to determine the photoprotective ability of the formulation. The cream met the requirements for desirable physical characteristics and provided moderate to good UV protection according to traditional skin care practices that use Aloe vera. This study suggests that Aloe vera-based topical formulations can serve as effective, natural photoprotective agents and provide a promising alternative to synthetic sunscreens.